Utilization of Outpatient Physical and Occupational Therapy in People With Spinal Cord Injury in Germany: Results of the German Spinal Cord Injury Survey. (June 2020) - Martini, Luiza; Maus, Uwe; Bökel, Andrea; Geng, Veronika; Kalke, Yorck-Bernhard; Liebscher, Thomas; Weidner, Norbert; Hoffmann, Falk
Abstract : Objective: The aim of the study was to assess factors determining the utilization of physical and occupational therapy in people with spinal cord injury. Design: Data from the German Spinal Cord Injury study conducted in 2017 were analyzed. The 12-mo prevalence of physical therapy and occupational therapy utilization was determined. To identify underlying determinants, multivariable logistic regression was used. Results: Of 1479 participants (response = 26.4%), 72.9% were male, with a mean (SD) age of 55.3 (14.6) yrs and a mean (SD) time since injury of 14.0 (12.0) yrs; 51.2% were people with paraplegia and 66.3% had an incomplete spinal cord injury. In the past 12 mos, 78.1% received physical and 29.3% occupational therapy. Physical therapy and occupational therapy were significantly associated with time since spinal cord injury occurrence, participation in lifelong care programs, and electric wheelchair dependency. Spinal cord injury characteristics, level of impairment, and time since spinal cord injury had a greater impact on occupational therapy than on physical therapy utilization. Conclusions: The use of physical therapy and occupational therapy is much higher in Germans with spinal cord injury than in the general population and in people with similar neurological conditions. Further research should focus on the frequency of use and the types of interventions. Guidelines for lifelong care should include recommendations on physical therapy and occupational therapy. Abstract : Supplemental digital content is available in the text.